Coal gangue-based waterproof ceramic tile adhesive and preparation method thereof

By using silica-coated modified fiber materials and mildew-resistant modified vinyl acetate-ethylene copolymer, the structural deterioration problem of coal gangue-based adhesives in high humidity and heat environments was solved, and the resistance to humidity and heat and mildew resistance were improved.

CN120864845AActive Publication Date: 2025-10-31安徽淮海新材料有限责任公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511401380.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-28
Publication Date
2025-10-31
Estimated Expiration
2045-09-28

AI Technical Summary

Technical Problem

Coal gangue-based adhesives are prone to structural deterioration due to moisture penetration in high humidity and heat environments, resulting in reduced bonding strength and tile detachment.

Method used

Silica-coated modified fiber material is used to seal decarburized coal gangue, forming a fiber-doped coal gangue compound powder. Anti-mildew modified vinyl acetate-ethylene copolymer is added to form a continuous sealing layer, which improves resistance to damp heat and mildew resistance.

Benefits of technology

It effectively prevents water molecules from penetrating, enhances the adhesive's resistance to moisture and heat and its anti-mildew properties, improves the bonding strength and anti-mildew performance of tiles, and prevents aging and detachment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a coal gangue-based waterproof ceramic tile adhesive and a preparation method thereof, and belongs to the technical field of building materials, silicon dioxide is utilized to coat a modified fiber material, so that the modified fiber material can uniformly block decarburized coal gangue, and the silicon dioxide contained in the structure can make water molecules difficult to permeate into the structure, so that the water-proof performance of the ceramic tile adhesive is improved. When the coating is applied to a high-humidity and high-heat environment, aging caused by invasion of water can be avoided; the silicon dioxide can be beneficial to hydration, calcium silicate gel and ettringite can be generated through hydration, ettringite is a needle-shaped substance, has expansibility and can be inserted into the gel to serve as an early reinforcing phase, ettringite crystals can grow towards a gel matrix along gaps, channels can be formed through expansion, and therefore the effect that the ettringite can be used as an early reinforcing phase is achieved. Further, the modified fiber material is guided to be inserted into the gel, the strength of the gel is improved, silicon dioxide is indirectly anchored in the gel through the insertion effect to avoid falling off, and the heat and humidity resistance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building materials technology, specifically a coal gangue-based waterproof ceramic brick adhesive and its preparation method. Background Technology

[0002] Coal gangue is a dark gray rock with low carbon content and high hardness that coexists with coal seams during the coal formation process. Currently, the total amount of coal gangue stockpiled in my country has exceeded 4.5 billion tons, and it is increasing at a rate of nearly 400 million tons per year. Coal gangue stockpiling is rampant, with nearly 2,000 large-scale gangue mountains covering an area of ​​more than 13,000 hectares, and this area is increasing by 400 hectares per year. How to comprehensively utilize coal gangue solid waste in a resource-based, large-scale, and harmless manner is an important issue facing scientific and technological personnel.

[0003] Coal gangue contains over 80% silicon and aluminum, making it a natural raw material for cementitious materials. Coal gangue gel materials are one pathway for the resource utilization of coal gangue solid waste. Chinese patent announcement CN117069399B discloses a cementitious material based on coal gangue solid waste and its preparation method. By controlling the content of free calcium oxide in the alkali activator to 8%–10%, a large amount of free calcium oxide can react fully with more active SiO2 and Al2O3 in the modified coal gangue, yielding more tricalcium silicate and dicalcium silicate, which can improve the mechanical properties of the cementitious material.

[0004] Coal gangue gel material is the core component of coal gangue tile adhesive, but in practical applications, especially when the coal gangue content in the adhesive is high, its material properties can cause a series of durability problems.

[0005] Specifically, coal gangue powder exhibits significant water absorption due to its numerous microcracks and high porosity. When such adhesives are used for bonding tiles in high-humidity and heat environments such as boiler rooms and bathrooms, water molecules easily penetrate the material through the pores, causing hydration reactions or water absorption and expansion in the cementitious system. Prolonged exposure to a humid environment leads to gradual deterioration of the material's internal structure due to repeated wet-dry cycles, resulting in cementitious material aging, decreased bonding strength, and ultimately, tile hollowing or even detachment, severely impacting the safety and durability of building decorations. Summary of the Invention

[0006] The purpose of this invention is to provide a coal gangue-based waterproof ceramic brick adhesive and its preparation method. Modified fiber materials are coated with silica to uniformly seal decarburized coal gangue, resulting in a fiber-doped coal gangue compound powder. This powder is used as a filler in the adhesive. The silica in the powder has high bond energy and a three-dimensional network structure, making it difficult for water molecules to penetrate the internal structure, allowing them to act only on the surface and preventing damage to the internal structure. When applied in the high humidity and heat environment of boiler rooms and bathrooms, it can prevent water intrusion that could lead to aging.

[0007] The objective of this invention can be achieved through the following technical solutions: A method for preparing a coal gangue-based waterproof ceramic brick adhesive includes the following steps: Step 1: The fiber material is pretreated by washing it with anhydrous ethanol and acetone, and then coated with polydopamine to obtain the modified fiber material.

[0008] Step 2: Microcracks in decarburized coal gangue powder are filled with nano-silica using the sol-gel method, and modified fiber material is used as the reinforcing phase to obtain fiber-doped coal gangue composite powder.

[0009] Step 3: Mix coal gangue-based solid waste cement, fiber-doped coal gangue compound powder, mildew-resistant modified vinyl acetate-ethylene copolymer, fatty acid-based water-reducing agent and reinforcing agent to obtain coal gangue-based waterproof ceramic brick adhesive.

[0010] Furthermore, the ratio of the following components is as follows: coal gangue-based solid waste cement, fiber-doped coal gangue compound powder, mildew-resistant modified vinyl acetate-ethylene copolymer, fatty acid-based water-reducing agent, and reinforcing agent: 20-30 parts: 50-60 parts: 4-5 parts: 3-4 parts: 1-2 parts.

[0011] Furthermore, the reinforcing agent is any one or a combination of calcium chloride, sodium aluminate, sodium carbonate, sodium formate, triethanolamine, and calcium formate.

[0012] Furthermore, coal gangue-based solid waste cement is silicate cement produced by a dry rotary kiln process at 1300℃ using coal gangue, high-calcium tailings, and quartz tailings as raw materials in a mass ratio of 2:0.5:0.3.

[0013] Furthermore, the specific preparation steps for the pretreated fiber material are as follows: Fiber material with a diameter of 7-8 μm, anhydrous ethanol and acetone are added to a reaction vessel and stirred for 10-20 min at 20-25℃ and 500-600 r / min. The fiber material is then placed in a drying oven and dried at 60-80℃ for 1-2 h to obtain pretreated fiber material.

[0014] Furthermore, the ratio of fiber material, anhydrous ethanol, and acetone used is 15-16g: 50-60mL: 80-90mL.

[0015] Furthermore, the fiber material is any one or more of hydroxypropyl methylcellulose, hydroxyethyl cellulose, polypropylene fiber, polyvinyl alcohol fiber, and glass fiber in any ratio.

[0016] Furthermore, the specific preparation steps for the modified fiber material are as follows: The pretreated fiber material and deionized water were added to a reaction vessel and stirred for 10-20 min at 20-25℃ and 500-600 r / min. The pH value was adjusted to 8-9 with NaOH solution, and then dopamine hydrochloride powder and anhydrous ethanol were added. Stirring was continued for 24-26 h under light-protected conditions. The mixture was filtered, and the product was washed 2-3 times with deionized water and anhydrous ethanol, respectively. The product was then vacuum dried at 60-80℃ for 1-2 h to obtain the modified fiber material.

[0017] Furthermore, the ratio of pretreated fiber material, deionized water, dopamine hydrochloride powder, and anhydrous ethanol is 12-14g: 20-30mL: 16-18mg: 10-12mL.

[0018] Furthermore, the specific preparation steps for fiber-doped coal gangue composite powder are as follows: Modified fiber material, ethanol, deionized water and ammonia water are added to a reaction vessel and stirred for 10-20 min at 20-25℃ and 500-600 r / min. Then, tetraethyl orthosilicate is added and stirring is continued for 2-3 h. Then, decarburized coal gangue is added and stirring is continued for 1-2 h. The mixture is filtered and the product is washed 2-3 times with deionized water and anhydrous ethanol, respectively. It is then vacuum dried at 60-80℃ for 1-2 h to obtain fiber-doped coal gangue compound powder.

[0019] Furthermore, the ratio of modified fiber material, ethanol, deionized water, ammonia, tetraethyl orthosilicate and decarburized coal gangue is 1-1.5g: 90-100mL: 120-140mL: 15-16mL: 15-16mL: 80-90g.

[0020] Furthermore, the specific preparation steps of the modified vinyl acetate-ethylene copolymer are as follows: 4-Vinyl-1,2-phthalic acid, dicumyl peroxide, and acetone were added to a reaction vessel and stirred for 10-20 minutes at 20-25°C and 500-600 r / min. Then, vinyl acetate-ethylene copolymer was added, and the mixture was heated to 170-180°C and stirred for another 10-20 minutes to obtain modified vinyl acetate-ethylene copolymer.

[0021] Furthermore, the ratio of 4-vinyl-1,2-phthalic acid, dicumyl peroxide, acetone, and vinyl acetate-ethylene copolymer is 20-25g: 0.6-0.8g: 80-90mL: 50-60g.

[0022] Furthermore, the specific preparation steps for the anti-mildew modified vinyl acetate-ethylene copolymer are as follows: Polyphosphoric acid, benzyl tetramine, isophthalic acid, and modified vinyl acetate-ethylene copolymer were added to a reaction vessel and stirred for 10-20 min at 20-25℃ and 500-600 r / min. Under a nitrogen atmosphere, the mixture was heated to 140-150℃ and stirred for 2-3 h. Then, it was heated to 200-220℃ and reacted for 6-7 h. After filtration, the product was soaked in a 30-40% sodium bicarbonate solution for 24-26 h to remove residual acid. The product was then vacuum dried at 60-80℃ for 1-2 h to obtain the anti-mildew modified vinyl acetate-ethylene copolymer.

[0023] Furthermore, the ratio of polyphosphoric acid, benzyl tetramine, isophthalic acid and modified vinyl acetate-ethylene copolymer is 70-80g: 20-30g: 22-25g: 50-60g.

[0024] The beneficial effects of this invention are: 1. The waterproof ceramic tile adhesive prepared by this invention utilizes silica to coat modified fiber materials, enabling them to uniformly seal decarburized coal gangue, resulting in fiber-doped coal gangue compound powder, which is used as a filler in the adhesive. The silica contained in its structure has high bond energy and a three-dimensional network structure, making it difficult for water molecules to penetrate into the structure and preventing damage to the internal structure. When applied in the high humidity and heat environment of boiler rooms and bathrooms, it can prevent aging caused by water intrusion.

[0025] 2. The fiber-doped coal gangue compound powder of the present invention has silica in its structure that can provide a silicon source, which is beneficial to the hydration with cement. The hydration can generate calcium silicate gel and ettringite in the gap between coal gangue and cement. The ettringite is a needle-like substance with expansion properties, which can be inserted into the gel as an early reinforcing phase. At the same time, the needle-like ettringite crystals will grow into the gel matrix along the gap. The expansion can form channels, which will lead to increased water absorption. However, the modified fiber material will penetrate into the gel through the guidance of the channels, reduce porosity, and increase the strength of the gel. Since the surface of the modified fiber material contains silica, the penetration indirectly anchors the silica in the gel to prevent it from falling off, which further improves the resistance to damp heat.

[0026] 3. The modified fiber material of the present invention is formed by the self-polymerization of dopamine molecules on the surface of the fiber material, which is firmly attached to the fiber surface by intermolecular hydrogen bonding. At the same time, the introduction of amino and catechol groups significantly improves the reactivity and affinity of the fiber surface. These groups can form hydrogen bonds with the silanols produced by the hydrolysis of tetraethyl orthosilicate, and the introduced amino groups can catalyze the hydrolysis and condensation reaction of tetraethyl orthosilicate, so that silica preferentially nucleates on the surface of the modified fiber material.

[0027] 4. The waterproof ceramic tile adhesive of the present invention incorporates a mildew-resistant modified vinyl acetate-ethylene copolymer, giving the waterproof ceramic tile adhesive mildew resistance and preventing mold growth in humid environments. The mildew-resistant modified vinyl acetate-ethylene copolymer is essentially produced by polymerizing the double bonds of vinyl benzoic acid with the double bonds in the vinyl acetate-ethylene copolymer, introducing carboxyl sites onto the surface of the vinyl acetate-ethylene copolymer. The carboxyl sites guide the process of biphenyltetramine and isophthalic acid to form a polymer chain containing triazole rings through condensation polymerization. The triazole rings have mildew-resistant properties and, in synergy with fiber-doped coal gangue compound powder, improve mold growth under humid and hot conditions. As a core bonding component, the mildew-resistant modified vinyl acetate-ethylene copolymer can fill the capillary pores and microcracks generated by cement curing shrinkage, forming a continuous sealing layer and improving the strength of cement curing. Detailed Implementation

[0028] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0029] Example 1: A method for preparing a coal gangue-based waterproof ceramic brick adhesive, comprising the following steps: S1: Add 15g of fiber material (polyvinyl alcohol fiber) with a diameter of 7-8μm, 50mL of anhydrous ethanol and 80mL of acetone to a reaction vessel, stir for 10min at 20℃ and 500r / min, and dry the fiber material in a drying oven at 60℃ for 1h to obtain pretreated fiber material; Add 12g of pretreated fiber material and 20mL of deionized water to a reaction vessel, stir for 10min at 20℃ and 500r / min, adjust the pH value to 8 with NaOH solution, then add 16mg of dopamine hydrochloride powder and 10mL of anhydrous ethanol, continue stirring for 24h under light-protected conditions, filter, wash the product twice with deionized water and anhydrous ethanol respectively, and vacuum dry at 60℃ for 1h to obtain modified fiber material.

[0030] The fiber material is immersed in anhydrous ethanol and acetone to wash away surface impurities, resulting in a pretreated fiber material. Dopamine is then polymerized on the surface of the pretreated fiber material through hydrogen bonding to obtain a modified fiber material.

[0031] S2: Add 1g of modified fiber material, 90mL of ethanol, 120mL of deionized water and 15mL of ammonia water to a reaction vessel, stir for 10min at 20℃ and 500r / min, then add 15mL of tetraethyl orthosilicate, continue stirring for 2h, then add 80g of decarburized coal gangue with a particle size of 80-90μm, continue stirring for 1h, filter, wash the product twice with deionized water and anhydrous ethanol respectively, and vacuum dry at 60℃ for 1h to obtain fiber-doped coal gangue composite powder.

[0032] The polydopamine layer on the surface of the modified fiber material can act as a medium to introduce amino and catechol groups. The amino and catechol groups can form hydrogen bonds with the silanols produced by the hydrolysis of tetraethyl orthosilicate, causing silica to be deposited on the surface of the modified fiber. Then, through the physical adsorption and hydrogen bonding of decarburized coal gangue, fiber-doped coal gangue composite powder is obtained.

[0033] S3: Add 20g of 4-vinyl-1,2-phthalic acid, 0.6g of dicumyl peroxide and 80mL of acetone to a reaction vessel, stir for 10min at 20℃ and 500r / min, then add 50g of vinyl acetate-ethylene copolymer, heat to 170℃, and continue stirring for 10min to obtain modified vinyl acetate-ethylene copolymer.

[0034] The vinyl groups contained in 4-vinyl-1,2-phthalic acid are copolymerized with the double bonds in vinyl acetate-ethylene copolymer under the action of dicumyl peroxide to obtain modified vinyl acetate-ethylene copolymer.

[0035] S4: Add 70g polyphosphoric acid, 20g benzyl tetramine, 22g isophthalic acid and 50g modified vinyl acetate-ethylene copolymer to a reactor, stir for 10min at 20℃ and 500r / min, heat to 140℃ under nitrogen atmosphere, continue stirring for 2h, then heat to 200℃ and continue reacting for 6h, filter, soak the product in a 30% sodium bicarbonate solution for 24h to remove residual acid, and vacuum dry at 60℃ for 1h to obtain anti-mildew modified vinyl acetate-ethylene copolymer.

[0036] Using polyphosphoric acid as a solvent, the dicarboxyl groups in the modified vinyl acetate-ethylene copolymer and isophthalic acid are condensed with the diamino group of benzyl tetramine to obtain a polymer chain containing a triazole ring, which is then formed on the antifungal modified vinyl acetate-ethylene copolymer.

[0037] S5: By weight, 20 parts of coal gangue-based solid waste cement, 50 parts of fiber-doped coal gangue compound powder, 4 parts of mildew-resistant modified vinyl acetate-ethylene copolymer, 3 parts of fatty acid-based water-reducing agent and 1 part of reinforcing agent are added to a mixer and mixed at a speed of 24 r / min for 15 min. After mixing, the following steps are performed in sequence: discharge, inspection, measurement, sealing and packaging, to obtain a coal gangue-based waterproof ceramic brick adhesive.

[0038] Example 2: A method for preparing a coal gangue-based waterproof ceramic brick adhesive, comprising the following steps: S1: 15.5g of fiber material (polyvinyl alcohol fiber) with a diameter of 7-8μm, 55mL of anhydrous ethanol and 85mL of acetone were added to a reaction vessel and stirred for 15min at 22.5℃ and 550r / min. The fiber material was then dried in a drying oven at 70℃ for 1.5h to obtain pretreated fiber material. 13g of pretreated fiber material and 25mL of deionized water were added to a reaction vessel and stirred for 15min at 22.5℃ and 550r / min. The pH was adjusted to 8.5 with NaOH solution, and then 17mg of dopamine hydrochloride powder and 11mL of anhydrous ethanol were added. The mixture was stirred for 25h under light-protected conditions, filtered, and the product was washed 2.5 times with deionized water and anhydrous ethanol, respectively. The product was then vacuum dried at 70℃ for 1.5h to obtain modified fiber material.

[0039] S2: Add 1.25g of modified fiber material, 95mL of ethanol, 130mL of deionized water and 15.5mL of ammonia water to a reaction vessel, stir for 15min at 22.5℃ and 550r / min, then add 15.5mL of tetraethyl orthosilicate, continue stirring for 2.5h, then add 85g of decarburized coal gangue with a particle size of 80-90μm, continue stirring for 1.5h, filter, wash the product 2.5 times with deionized water and anhydrous ethanol respectively, and vacuum dry at 70℃ for 1.5h to obtain fiber-doped coal gangue composite powder.

[0040] S3: Add 22.5g of 4-vinyl-1,2-phthalic acid, 0.7g of dicumyl peroxide and 85mL of acetone to a reaction vessel, stir for 15min at 22.5℃ and 550r / min, then add 55g of vinyl acetate-ethylene copolymer, heat to 175℃, and continue stirring for 15min to obtain modified vinyl acetate-ethylene copolymer.

[0041] S4: Add 75g polyphosphoric acid, 25g benzyl tetramine, 23.5g isophthalic acid and 55g modified vinyl acetate-ethylene copolymer to a reaction vessel, stir for 15min at 22.5℃ and 550r / min, heat to 145℃ under nitrogen atmosphere, continue stirring for 2.5h, then heat to 210℃ and continue reacting for 6.5h, filter, soak the product in a 35% sodium bicarbonate solution for 25h to remove residual acid, and vacuum dry at 70℃ for 1.5h to obtain anti-mildew modified vinyl acetate-ethylene copolymer.

[0042] S5: By weight, 20 parts of coal gangue-based solid waste cement, 50 parts of fiber-doped coal gangue compound powder, 4.5 parts of mildew-resistant modified vinyl acetate-ethylene copolymer, 3.5 parts of fatty acid-based water-reducing agent, and 1.5 parts of reinforcing agent are added to a mixer and mixed at a speed of 25 r / min for 17.5 min. After mixing, the following steps are performed in sequence: discharge, inspection, measurement, sealing, and packaging to obtain a coal gangue-based waterproof ceramic brick adhesive.

[0043] Example 3: A method for preparing a coal gangue-based waterproof ceramic brick adhesive, comprising the following steps: S1: 16g of fiber material (polyvinyl alcohol fiber) with a diameter of 7-8μm, 60mL of anhydrous ethanol and 90mL of acetone were added to a reaction vessel and stirred for 20min at 25℃ and 600r / min. The fiber material was then dried in a drying oven at 80℃ for 2h to obtain pretreated fiber material. 14g of pretreated fiber material and 30mL of deionized water were added to a reaction vessel and stirred for 20min at 25℃ and 600r / min. The pH was adjusted to 9 with NaOH solution, and then 18mg of dopamine hydrochloride powder and 12mL of anhydrous ethanol were added. The mixture was stirred for 26h under light-protected conditions, filtered, and the product was washed three times with deionized water and anhydrous ethanol, respectively. The product was then vacuum dried at 80℃ for 2h to obtain modified fiber material.

[0044] S2: Add 1.5g of modified fiber material, 100mL of ethanol, 140mL of deionized water and 16mL of ammonia water to a reaction vessel, stir for 20min at 25℃ and 600r / min, then add 16mL of tetraethyl orthosilicate, continue stirring for 3h, then add 90g of decarburized coal gangue with a particle size of 80-90μm, continue stirring for 2h, filter, wash the product three times with deionized water and anhydrous ethanol respectively, and vacuum dry at 80℃ for 2h to obtain fiber-doped coal gangue composite powder.

[0045] S3: Add 25g of 4-vinyl-1,2-phthalic acid, 0.8g of dicumyl peroxide and 90mL of acetone to a reaction vessel, stir for 20min at 25℃ and 600r / min, then add 60g of vinyl acetate-ethylene copolymer, heat to 180℃, and continue stirring for 20min to obtain modified vinyl acetate-ethylene copolymer.

[0046] S4: Add 80g of polyphosphoric acid, 30g of benzyl tetramine, 25g of isophthalic acid and 60g of modified vinyl acetate-ethylene copolymer to a reactor, stir for 20min at 25℃ and 600r / min, heat to 150℃ under nitrogen atmosphere, continue stirring for 3h, then heat to 220℃ and continue reacting for 7h, filter, soak the product in a 40% sodium bicarbonate solution for 26h to remove residual acid, and vacuum dry at 80℃ for 2h to obtain anti-mildew modified vinyl acetate-ethylene copolymer.

[0047] S5: By weight, 20 parts of coal gangue-based solid waste cement, 50 parts of fiber-doped coal gangue compound powder, 5 parts of mildew-resistant modified vinyl acetate-ethylene copolymer, 4 parts of fatty acid-based water-reducing agent and 2 parts of reinforcing agent are added to a mixer and mixed at a speed of 26 r / min for 20 min. After mixing, the following steps are performed in sequence: discharge, inspection, measurement, sealing and packaging, to obtain a coal gangue-based waterproof ceramic brick adhesive.

[0048] Comparative Example 1: Based on Example 3, the fiber-doped coal gangue compound powder in step S5 was replaced with commercially available decarburized coal gangue with a particle size of 80-90μm, while the other steps remained unchanged, to prepare a coal gangue-based waterproof ceramic brick adhesive.

[0049] Comparative Example 2: Based on Example 3, the modified fiber material in step S2 was replaced with the pretreated fiber material in step S1, while the other steps remained unchanged, to prepare a coal gangue-based waterproof ceramic brick adhesive.

[0050] Comparative Example 3: Based on Example 3, the modified vinyl acetate-ethylene copolymer in step S4 was replaced with the raw material vinyl acetate-ethylene copolymer in step S3, while the other steps remained unchanged, to prepare a coal gangue-based waterproof ceramic brick adhesive.

[0051] In the examples and comparative examples: Coal gangue-based solid waste cement is silicate cement produced by a dry rotary kiln process at 1300℃ using coal gangue, high-calcium tailings, and quartz tailings as raw materials in a mass ratio of 2:0.5:0.3. The fiber material is any one or more of hydroxypropyl methylcellulose, hydroxyethyl cellulose, polypropylene fiber, polyvinyl alcohol fiber, and glass fiber in any proportion. In the above examples and comparative examples, polyvinyl alcohol fiber is used, and the fiber length is 4-6 mm. The reinforcing agent is any one or more of calcium chloride, sodium aluminate, sodium carbonate, sodium formate, triethanolamine, and calcium formate in any proportion. In the above examples and comparative examples, sodium formate is used.

[0052] The performance of the waterproof ceramic tile adhesives prepared in Examples 1-3 and Comparative Examples 1-3 was tested. Cement samples with a curing period of 90 days were tested in accordance with the standards of JC / T547-2005 "Ceramic Wall and Floor Tile Adhesives" and GB / T17671-1999 "Test Method for Strength of Cement Mortar". The results are shown in Table 1. The anti-mold performance of waterproof ceramic tile adhesive was tested according to the method in QB / T2591-2003. The test strain was a composite mold containing Aspergillus niger, Chaetomium globosum, Penicillium cordifolium, and Aspergillus terreus. The mold growth grade of the samples was as follows: grade 0 was no mold growth; grade 1 was trace growth; the mold growth coverage area was ≤10%; and grade 2 was ≥10% of the mold growth coverage area. The results are shown in Table 2. Table 1. Performance Test Results of Waterproof Ceramic Tile Adhesive

[0053] Table 2. Test Table of Anti-mildew Performance of Waterproof Ceramic Tile Adhesive

[0054] As can be seen from Tables 1 and 2, the tensile adhesive strength, flexural strength and compressive strength of the waterproof ceramic tile adhesives prepared in Examples 1-3 are significantly better than those of the comparative examples, while the water absorption, mold growth and anti-mold level are significantly lower than those of the comparative examples. This indicates that the waterproof ceramic tile adhesive prepared in this invention has the properties of resistance to humid heat aging and anti-mold, and also has excellent strength.

[0055] In Comparative Example 1, the fiber-doped coal gangue compound powder was replaced with commercially available decarburized coal gangue. Commercially available decarburized coal gangue is porous, and the formation of ettringite during hydration can further increase the porosity. This process has little impact on the initial strength, but the entry of moisture in a humid and hot environment will significantly reduce the strength, leading to the aging and detachment of the adhesive.

[0056] Comparative Example 2 replaced the modified fiber material with a pretreated fiber material. The pretreated fiber material had no dopamine coating on its surface, so it could not form hydrogen bonds with the silanols hydrolyzed from tetraethyl orthosilicate. This made it difficult for silica to nucleate on the fiber surface, and it was easy for silica to self-aggregate in the solution to form free particles, which could not form a continuous coating layer. The fiber surface without dopamine modification had no active groups, so it could not induce the directional growth of ettringite. The ettringite was only generated randomly, and the combination of fiber and gel relied only on physical entanglement. It was easy to be pulled out under stress. The adhesive was prone to micro-cracks due to shrinkage, which further aggravated water penetration. The uneven silica coating meant that the interface gaps between the fiber and coal gangue could not be effectively filled by ettringite. Water molecules could easily penetrate from the gaps, and after the tiles were laid, they were prone to slippage, resulting in hollowing and falling off.

[0057] Comparative Example 3 replaced the modified vinyl acetate-ethylene copolymer with vinyl acetate-ethylene copolymer without vinyl benzoic acid grafting modification. This resulted in the inability to graft the subsequently generated triazole ring structure into the vinyl acetate-ethylene copolymer structure, leading to a decrease in anti-mold effect. In humid environments, the organic acids secreted by mold corrode the cement gel and fibers, causing the adhesive structure to crumble. Mold erosion destroys the three-dimensional network structure of the gel and causes debonding at the fiber-gel interface.

[0058] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention.

Claims

1. A method for preparing a coal gangue-based waterproof ceramic brick adhesive, characterized in that, Includes the following steps: Step 1: The fiber material is pretreated by washing it with anhydrous ethanol and acetone, and then coated with polydopamine to obtain the modified fiber material. Step 2: Microcracks in decarburized coal gangue powder are filled with nano-silica using the sol-gel method, and modified fiber material is used as the reinforcing phase to obtain fiber-doped coal gangue composite powder. Step 3: Mix coal gangue-based solid waste cement, fiber-doped coal gangue compound powder, mildew-resistant modified vinyl acetate-ethylene copolymer, fatty acid-based water-reducing agent and reinforcing agent to obtain coal gangue-based waterproof ceramic brick adhesive.

2. The preparation method of the coal gangue-based waterproof ceramic brick adhesive according to claim 1, characterized in that, The mass ratio of the coal gangue-based solid waste cement, fiber-doped coal gangue compound powder, mildew-resistant modified vinyl acetate-ethylene copolymer, fatty acid-based water-reducing agent, and reinforcing agent is 20-30:50-60:4-5:3-4:1-2.

3. The preparation method of the coal gangue-based waterproof ceramic brick adhesive according to claim 1, characterized in that, The specific preparation steps for the pretreated fiber material are as follows: Add 7-8 μm diameter fiber material, anhydrous ethanol and acetone to a reaction vessel, stir for 10-20 min at 20-25℃ and 500-600 r / min, and then dry the fiber material in a drying oven at 60-80℃ for 1-2 h to obtain pretreated fiber material. The ratio of the fiber material, anhydrous ethanol, and acetone used is 15-16g: 50-60mL: 80-90mL.

4. The preparation method of the coal gangue-based waterproof ceramic brick adhesive according to claim 1, characterized in that, The specific preparation steps of the modified fiber material are as follows: The pretreated fiber material and deionized water were added to a reaction vessel and stirred at 20-25℃ and 500-600 r / min for 10-20 min. The pH value was adjusted to 8-9 with NaOH solution, and then dopamine hydrochloride powder and anhydrous ethanol were added. Stirring was continued for 24-26 h under light-protected conditions. The mixture was then filtered, washed, and vacuum dried to obtain the modified fiber material.

5. The preparation method of a coal gangue-based waterproof ceramic brick adhesive according to claim 4, characterized in that, The ratio of the pretreated fiber material, deionized water, dopamine hydrochloride powder, and anhydrous ethanol is 12-14g: 20-30mL: 16-18mg: 10-12mL.

6. The preparation method of a coal gangue-based waterproof ceramic brick adhesive according to claim 1, characterized in that, The specific preparation steps for the fiber-doped coal gangue composite powder are as follows: Modified fiber material, ethanol, deionized water and ammonia water are added to a reaction vessel and stirred at 20-25℃ and 500-600r / min for 10-20min. Then, tetraethyl orthosilicate is added and stirring is continued for 2-3h. Then, decarburized coal gangue is added and stirring is continued for 1-2h. The mixture is then filtered, washed and vacuum dried to obtain fiber-doped coal gangue composite powder. The ratio of the modified fiber material, ethanol, deionized water, ammonia, tetraethyl orthosilicate and decarbonized coal gangue is 1-1.5g: 90-100mL: 120-140mL: 15-16mL: 15-16mL: 80-90g.

7. The preparation method of a coal gangue-based waterproof ceramic brick adhesive according to claim 1, characterized in that, The specific preparation steps of the modified vinyl acetate-ethylene copolymer are as follows: 4-Vinyl-1,2-phthalic acid, dicumyl peroxide and acetone were added to a reaction vessel and stirred at 20-25°C and 500-600 r / min for 10-20 min. Then vinyl acetate-ethylene copolymer was added, heated to 170-180°C and stirred for another 10-20 min to obtain modified vinyl acetate-ethylene copolymer. The ratio of 4-vinyl-1,2-phthalic acid, dicumyl peroxide, acetone, and vinyl acetate-ethylene copolymer is 20-25g: 0.6-0.8g: 80-90mL: 50-60g.

8. The preparation method of a coal gangue-based waterproof ceramic brick adhesive according to claim 1, characterized in that, The specific preparation steps of the anti-mildew modified vinyl acetate-ethylene copolymer are as follows: Polyphosphoric acid, biphenyltetramine, isophthalic acid, and modified vinyl acetate-ethylene copolymer were added to a reaction vessel and stirred at 20-25°C and 500-600 r / min for 10-20 min. Under a nitrogen atmosphere, the mixture was heated to 140-150°C and stirred for 2-3 h. Then, it was heated to 200-220°C and reacted for another 6-7 h. After filtration, the product was soaked in a 30-40 wt% sodium bicarbonate solution for 24-26 h to remove residual acid. The product was then vacuum dried to obtain the anti-mildew modified vinyl acetate-ethylene copolymer.

9. The preparation method of a coal gangue-based waterproof ceramic brick adhesive according to claim 8, characterized in that, The ratio of polyphosphoric acid, biphenyltetramine, isophthalic acid and modified vinyl acetate-ethylene copolymer is 70-80g: 20-30g: 22-25g: 50-60g.

10. A coal gangue-based waterproof ceramic brick adhesive, characterized in that, It is prepared by the preparation method described in any one of claims 1-9.

Citation Information

Patent Citations

  • A cementitious material based on coal gangue solid waste and a preparation method thereof

    CN117069399B

  • Composite phosphogypsum-based ceramic tile adhesive and preparation method thereof

    CN118221415A

  • Method for preparing fiber-reinforced coal gangue-based composite functional aerogel

    CN120662215A

  • Solid waste-based reinforced ceramic tile adhesive and preparation method therefor

    WO2025124213A1